Commodity Taxation and Regulatory Competition - Simone Moriconi; Pierre M. Picard; Skerdilajda Zanaj (Università Cattolica del Sacro Cuore, Dipartimento di Economia e Finanza (DISCE), 2015)
This paper studies competition in commodity taxation and product market regula- tion between trading partner countries. We present a two-country general equilibrium model in which destination-based commodity taxes finance public goods, and prod- uct market regulation affects both the number of firms in the market and product diversity. We provide empirical evidence based on data for 21 OECD countries over the 1990-2008 period. Our results suggest that commodity taxation and product mar- ket regulation are interdependent policies. Theoretically and empirically we find an absence of strategic interaction in commodity taxation between governments. Further- more, we show that domestic regulation has a negative effect on domestic commodity taxation. Finally, we demonstrate theoretically and show empirically that product market regulation is a strategic complementary policy.
Keywords: F0; H1; H7; H87; L5; 330; Regulation; commodity tax; strategic interactions